2021
DOI: 10.1039/d0np00023j
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoids from the medicinal mushroomAntrodia camphorata: chemistry and medicinal potential

Abstract: This review article summarizes the research progress on terpenoids from the medicinal mushroom Antrodia camphorata during 1995–2020, including structural diversity, resources, biosynthesis, pharmacological activities, metabolism, and toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 138 publications
0
62
0
2
Order By: Relevance
“…Recent studies have found that A. camphorata is rich in a variety of active compounds such as polysaccharides, triterpenoids, adenosine, polypeptides, vitamins, trace elements, nucleic acids, and sterols [11]. The ergostane-type triterpenoids was characteristic constituents of A. camphorata [19]. The ergostane-type triterpenoids (Antcin B, Antcin K and Antcin H) could protect against liver injury in vivo or vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that A. camphorata is rich in a variety of active compounds such as polysaccharides, triterpenoids, adenosine, polypeptides, vitamins, trace elements, nucleic acids, and sterols [11]. The ergostane-type triterpenoids was characteristic constituents of A. camphorata [19]. The ergostane-type triterpenoids (Antcin B, Antcin K and Antcin H) could protect against liver injury in vivo or vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Taiwanofungus camphoratus (Antrodia cinnamomea), often referred to as 'Niu-chang-chih', is a medicinal fungus that only grows on the native tree Cinnamomum kanehirai Hayata in Taiwan (7). Several bioactive compounds are present in Taiwanofungus camphoratus, including polysaccharides, triterpenes, diterpenes, succinic acid derivatives, and ubiquinone (7).…”
Section: Introductionmentioning
confidence: 99%
“…Taiwanofungus camphoratus (Antrodia cinnamomea), often referred to as 'Niu-chang-chih', is a medicinal fungus that only grows on the native tree Cinnamomum kanehirai Hayata in Taiwan (7). Several bioactive compounds are present in Taiwanofungus camphoratus, including polysaccharides, triterpenes, diterpenes, succinic acid derivatives, and ubiquinone (7). 4-Acetylantroquinonol B (4-AAQB) is the ubiquinone derivative of Taiwanofungus camphoratus, which is identified as the major antiproliferative compound for hepatoma cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a wealth of novel skeletons, biosynthetic pathways, and bioactivities have provided new opportunities for drug discovery, genome mining, enzymology, and chemical synthesis. During the period covered in this review, there have been several more specialized reviews of fungal metabolites [ 26 , 27 , 28 ], including benzene carbaldehydes [ 29 ], trichothecenes [ 30 , 31 ], protoilludane sesquiterpenoids [ 32 ], meroterpenoids [ 33 , 34 , 35 ], meroterpenoid cyclases [ 36 ], terpenoids [ 37 ], and natural product biosynthetic genes and enzymes of fungi [ 17 , 18 , 38 , 39 ]. In addition, the isolation and chemistry of diterpenoids from terrestrial sources have been summarized [ 40 ].…”
Section: Introductionmentioning
confidence: 99%